ANALISIS SISTEM SALURAN DRAINASE UNTUK PENANGGULANGAN BANJIR DI DESA MANAWA KAB POHUWATO - urfan (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2024)
This research aims to re-analyze existing drainage channels in order to find the right solution to overcome the amount of rainwater discharge so that it can match the drainage capacity so that it can overcome one of the causes of farmers' crop failure, especially those who work as corn farmers who are the majority in the area. agriculture in Rodji hamlet, Manawa village. In this research, the data used is secondary data in the form of hydrological data relating to rainfall on a 10 year time scale, starting from 2013 to 2022 and primary data in the form of channel dimensions in the Rodji hamlet area. And in the process of results and discussion, several methods were used that could possibly be studied more widely, and in the analysis results, the method used was the gumbel method which was chosen from four other methods. After carrying out further calculations, the selected result is the channel capacity over a period of 10 years using the Talbot method. The calculation results of the planned rainfall with a 10 year time scale with data on the dimensions of the drainage channels in the research area obtained a control discharge check = 7.738485 m3/second which is smaller than the planned discharge of 11.7743 m3/second so there must be an evaluation of the dimensions of the channel , and after carrying out evaluation research, the results obtained by checking the control discharge showed that the channel discharge = 13.67314 m³/second was greater than the planned discharge = 11.7743 m³/second, it is safe to use and can be a solution to flooding problems in the area.